The Effect of Environmental Accounting Disclosures on Firm Value With Environmental Performance as an Intervening Variable - Ni Made Prapti Anggreni K; Ni Made Dwi Ratnadi; Anak Agung Gde Putu Widanaputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Solving environmental problems is an issue that makes a company competitive advantage. One of the government's efforts to monitor and protect the environment is through the Company Performance Rating Program in Environmental Management (PROPER). This study aims to obtain empirical evidence regarding the effect of environmental accounting disclosures on firm value, the effect of environmental performance on firm value, the effect of environmental accounting disclosures on environmental performance and the effect of environmental accounting disclosures on firm value through environmental performance. The population is companies listed on the Sri Kehati Index 2016 – 2020. The method of determining the sample using purposive sampling technique using panel data (time series data and cross section) as many as 108 observations. The results show that environmental accounting disclosures affect firm value, environmental performance affects firm value, environmental accounting disclosures affect environmental performance and environmental accounting disclosures affect firm value through environmental performance. The implication is that it is very important to disclose transparent environmental accounting disclosures in the company's annual report because it can improve environmental performance and if investors react to it, the value of the company will increase.